Pengaruh Harga Dan Bukti Fisik Terhadap Keputusan Menginap di Rail Transit Suite Gambir - Kusumadewi, Isnaeni; Rustini, Rustini (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2024)
This research aimed to find out how much influence of price and physical evidence toward the decision to stay at the Gambir Rail Transit Suite. This research was motivated by some negative ulasans on the online travel agent Rail Transait Suite Gambir where guests who stayed there stated that the price of the stay was not commensurate with what they received and also complained about the physical evidence available. The method of this research was a quantitative method with data collection technique using questionnaires and observation. The population in this research was guests staying at the Rail Transit Suite Gambir. The number of samples successfully processed using the Slovin formula was 100 people who stayed at the Gambir Rail Transit Suite. The data analysis technique in this research used the validity test, classical assumption test, and multiple linear regression analysis with the t test and F test. Then the data was processed using the IBM SPSS 26 software program. The results of the coefficient of determination (R2) of this research showed the independent variable influenced the decision to stay partially (attached variable), namely price had a positive influence of 73.1% with t hitung value of 6.522 > t table 1.988 with significance value of 0.000 < 0.05 and physical evidence had a positive influence of 73.2% with t hitung value 6.553 > t table 1.988 with significance value of 0.000 < 0.05. Simultaneously, price and physical evidence had a positive influence on the decision to stay with F t hitung value of 211.382 > F table 3.09 with significance value of 0.000 < 0.05 and the coefficient of determination (R2) for price and physical evidence was 81%, while the remaining 19% was influenced by other variables not included in this research.